Early and midterm outcomes of thoracic endovascular aortic repair (TEVAR) for acute and chronic complicated type B aortic dissection - Zhang, Min-Hong (Medicine (Baltimore), 2017)
Thoracic endovascular aortic repair (TEVAR) in the current era has been chosen as a dominant and minimally invasive treatment for complicated aorta dissection. This study aimed to assess safety and feasibility of TEVAR in acute and chronic type B aortic dissection. Between January 2011 and December 2013, 85 patients with complicated type B aortic dissection undergoing TEVAR were divided into acute aortic dissection (AAD) (n = 60) group and chronic aortic dissection (CAD) group (n = 25). Computed tomography was used to evaluate postoperative changes in maximal aortic diameter and true and false lumen diameters at 3 levels during a mean follow-up period of 26.4 ± 15.6 months. The technical success rate was 100%. In-hospital and 30-day rates of death were 3.3% in acute group and 0 in chronic group. Postdischarge rates of type I leak, type II leak, and retrograde type A dissection were 6.7%, 5.2%, and 3.4% (acute) and 0%, 4.0%, and 4.0% (chronic), respectively. The maximal aorta diameter remained stable in all the 3 levels in both acute and chronic group. The cumulative freedom from all-cause mortality at 3 years was similar in acute and chronic groups (89.5% vs 95.5%, P = .308). The cumulative freedom from aortic-related mortality was also not significantly different in the acute and chronic groups (92.8% vs 95.2%, P = .531). In the thoracic aorta, TEVAR treatment resulted in a significant increase in true lumen (TL) diameter and decrease in false lumen (FL). However, in the abdominal aorta, TEVAR did not lead to significant change in TL and FL diameters. The rates of complete thrombosis thoracic false lumens were better than that in the abdominal false lumen. TEVAR was a safe and effect therapy for complicated acute and chronic type B dissection with low early and mid-term mortality and morbidity.